2017
DOI: 10.1038/s41598-017-10807-y
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolomics Signature Linked To Liver Fibrosis In The Serum Of Transplanted Hepatitis C Patients

Abstract: Liver fibrosis must be evaluated in patients with hepatitis C virus (HCV) after liver transplantation because its severity affects their prognosis and the recurrence of HCV. Since invasive biopsy is still the gold standard to identify patients at risk of graft loss from rapid fibrosis progression, it becomes crucial the development of new accurate, non-invasive methods that allow repetitive examination of the patients. Therefore, we have developed a non-invasive, accurate model to distinguish those patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…( 32 ) Similarly, in patients with HCV patients, Cano et al reported an increase in circulating levels of the primary conjugated bile acids TCDCA, TCA, and GCA in 69 subjects with F ≥ 2 compared to 134 subjects with F0‐F1. ( 33 ) Caussy et al also observed an increase in total bile acids, conjugated CA, and conjugated CDCA with increasing liver fibrosis stage. ( 34 ) Finally, Lelouvier et al reported a decrease in circulating LCA/CDCA, UDCA/CDCA, and TLCA/CDCA ratios in 11 obese subjects with fibrosis compared to 26 obese subjects without fibrosis, concluding that there may be a decreased capability to convert primary bile acids to secondary bile acids.…”
Section: Discussionmentioning
confidence: 97%
“…( 32 ) Similarly, in patients with HCV patients, Cano et al reported an increase in circulating levels of the primary conjugated bile acids TCDCA, TCA, and GCA in 69 subjects with F ≥ 2 compared to 134 subjects with F0‐F1. ( 33 ) Caussy et al also observed an increase in total bile acids, conjugated CA, and conjugated CDCA with increasing liver fibrosis stage. ( 34 ) Finally, Lelouvier et al reported a decrease in circulating LCA/CDCA, UDCA/CDCA, and TLCA/CDCA ratios in 11 obese subjects with fibrosis compared to 26 obese subjects without fibrosis, concluding that there may be a decreased capability to convert primary bile acids to secondary bile acids.…”
Section: Discussionmentioning
confidence: 97%
“…Severity of cirrhosis can also be monitored by serum metabolomics 27 . Similarly, different stages of liver fibrosis can be distinguished by their metabolomic fingerprint 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This is a challenging clinical need but of increasing interest in the light of precision medicine during systemic infections of different origin. Targeted metabolomics are an emerging field and can be used to diagnose or assess stages and severity of different liver diseases such as cirrhosis 26 , 27 and fibrosis 28 . We herein demonstrate that liver pathophysiology leads to distinct metabolomic fingerprint in sepsis due to the type and route of the pathogen and could be a useful tool for profiling of patients and subsequent customization and targeting of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the EAD group had a significantly lower level of long chain lysoPC (16:0) than the non-EAD group on postoperative day 7, demonstrating that a reduction in lysoPC correlates with the severity of liver disease. Cano et al [27] have recently demonstrated that increased levels of sphingomyelins and PC 16:0/16:0 and 16:0/18:0 may be linked to the severity of liver fibrosis in patients with hepatitis C virus (HCV) one year after transplantation. Similarly, we have demonstrated that specific metabolites, namely, PC 16:0/16:0, 16:0/18:1, 16:1/16:0, increased in the plasma levels in patients within 1 week after LDLT.…”
Section: Discussionmentioning
confidence: 99%